2008
DOI: 10.1149/1.2969433
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Binder Choice on the Performance of α-Fe[sub 2]O[sub 3] as a Negative Electrode

Abstract: The electrochemical performance of negative electrodes based on commercially available micrometer-sized ␣-Fe 2 O 3 powder and four different binders was investigated. ␣-Fe 2 O 3 electrodes made using sodium carboxymethyl cellulose binder and two proprietary binders show better cycling performance than electrodes made from the conventional binder, polyvinylidene fluoride ͑PVDF͒. Heat-treating the PVDF electrodes to 300°C improves electrode performance dramatically. A specific capacity of over 800 mAh/g for over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
116
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(125 citation statements)
references
References 27 publications
9
116
0
Order By: Relevance
“…9,[11][12][13][14] Furthermore, a selected binder, sodium carboxymethyl cellulose (CMC), can also improve cycling performance of a-Fe 2 O 3 at a low current density of 100 mA g À1 . 10 It is noticed that almost all the previous reports focused on very low rate charge/discharge current densities (about 0.1 C ¼ 100 mA g À1 ). It is still a great challenge to improve the high rate capability of iron oxide-base materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,[11][12][13][14] Furthermore, a selected binder, sodium carboxymethyl cellulose (CMC), can also improve cycling performance of a-Fe 2 O 3 at a low current density of 100 mA g À1 . 10 It is noticed that almost all the previous reports focused on very low rate charge/discharge current densities (about 0.1 C ¼ 100 mA g À1 ). It is still a great challenge to improve the high rate capability of iron oxide-base materials.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] As one of the promising anode materials, hematite (a-Fe 2 O 3 ) has been investigated intensively due to its great advantages such as high theoretical capacity (1007 mAh g À1 ), low cost, good stability, environmental friendliness, and high resistance to corrosion. [7][8][9][10][11][12][13][14][15] Recently, the capacity retention of iron oxide can be improved via fabricating active materials into hollow/nano-structures which could accommodate volume changes and shorten the lithium diffusion length. 9,[11][12][13][14] Furthermore, a selected binder, sodium carboxymethyl cellulose (CMC), can also improve cycling performance of a-Fe 2 O 3 at a low current density of 100 mA g À1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al demonstrated that binder choice and electrode pre-heat treatment could stabilize m-sized particles of aFe 2 O 3 with an active material loading of 80 % but required cycling at a lower rate of C/5 (five hours each for charge and discharge). [13] In order to accommodate for the high volume expansion of silicon, Kang et al coated Si particles with Co-Co 3 O 4 by solgel. [14] The coating improved the 12th cycle efficiency from 55 % to 88 % for micron-sized particles.…”
Section: Introductionmentioning
confidence: 99%
“…
Recently, electrochemically active metals and metal oxides, such as Sn, [1] Si, [2] Co 3 O 4 , [3,4] and Fe 2 O 3 , [5] have attracted much attention as anode materials for lithium ion batteries due to their high theoretical capacities and promising potential. However, a large specific volume change commonly occurs in the host matrix of these metals and metal oxides during the cycling process.
…”
mentioning
confidence: 99%